Regularity of zinc, copper, and lead distribution in different size fractions of Rostov-on-Don urban soil aggregates - S. S. Tagiverdiev; G. A. Plakhov; N. V. Salnik; O. S. Bezuglova; S. N. Gorbov (Бюллетень Почвенного института им. В.В. Докучаева, 2024)
: The article is devoted to the study of zinc, copper, and lead content in the soils of Rostov-on-Don. Soil samples were collected from full-profile sections located in different districts of the city and suburbs of Rostov-on-Don. The group of anthropogenically disturbed soils included Urbic Technosol urbanstratozems and replantozems, as well as urbanized chernozems Calcic Chernozems (Technic). Natural soils of recreational areas are represented by migration-segregation chernozems Calcic Chernozems (Pachic). The study was carried out using atomic absorption spectrometry and X-ray fluorescence analysis to determine metal content. Soil structure was determined by the Savvinov method (dry sieving) (<0.25; 1–2; 3–5; 5–7; >10 mm). Statistical analysis of the Wilcoxon criterion for related samples was performed to identify relationships. The main objective of the study was to assess the heavy metal content in different size fractions of aggregates and the ability of structural fractions to accumulate zinc, copper, and lead. Structural aggregates of different sizes differ in their ability to accumulate zinc, copper and lead. Zinc, including its mobile compounds, is predominantly accumulated in microaggregates. The content of gross copper and especially lead is confined to larger aggregates. At the same time, mobile copper compounds are concentrated in microaggregates and in fractions larger than 10 mm. Mobile lead compounds are distributed in fractions of different sizes quite uniformly in all studied soils.